Spectral modification of magnetar flares by resonant cyclotron scattering. Issue 1 (8th August 2020) - Yamasaki, Shotaro; Lyubarsky, Yuri; Granot, Jonathan; Göğüș, Ersin
ABSTRACT: Spectral modification of energetic magnetar flares by resonant cyclotron scattering (RCS) is considered. During energetic flares, photons emitted from the magnetically trapped fireball near the stellar surface should resonantly interact with magnetospheric electrons or positrons. We show by a simple thought experiment that such scattering particles are expected to move at mildly relativistic speeds along closed magnetic field lines, which would slightly shift the incident photon energy due to the Doppler effect. We develop a toy model for the spectral distortion by a single RCS that incorporates both a realistic seed photon spectrum from the trapped fireball and the velocity field of particles, which is unique to the flaring magnetosphere. We show that our spectral model can be effectively characterized by a single parameter: the effective temperature of the fireball, which enables us to fit observed spectra with low computational cost. We demonstrate that our single-scattering model is in remarkable agreement with Swift /BAT data of intermediate flares from SGR 1900+14, corresponding to effective fireball temperatures of T eff = 6–7 keV, whereas BeppoSAX /GRBM data of giant flares from the same source may need more elaborate models including the effect of multiple scatterings. Nevertheless, since there is no standard physically motivated model for magnetar flare spectra, our model could be a useful tool to study magnetar bursts, shedding light on the hidden properties of the flaring magnetosphere.